2014
DOI: 10.1073/pnas.1419553111
|View full text |Cite
|
Sign up to set email alerts
|

Recessive cardiac phenotypes in induced pluripotent stem cell models of Jervell and Lange-Nielsen syndrome: Disease mechanisms and pharmacological rescue

Abstract: Jervell and Lange-Nielsen syndrome (JLNS) is one of the most severe life-threatening cardiac arrhythmias. Patients display delayed cardiac repolarization, associated high risk of sudden death due to ventricular tachycardia, and congenital bilateral deafness. In contrast to the autosomal dominant forms of long QT syndrome, JLNS is a recessive trait, resulting from homozygous (or compound heterozygous) mutations in KCNQ1 or KCNE1. These genes encode the α and β subunits, respectively, of the ion channel conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 55 publications
9
162
1
1
Order By: Relevance
“…In addition, hiPSC‐CMs are also being used as model systems to test the effect of both known and novel drugs on cardiac channelopathies (Matsa et al , 2011; Zhang et al , 2012; Bellin et al , 2013; Di Pasquale et al , 2013; Zhang et al , 2014), with suppression of pathological pro‐arrhythmic potential and restoration of altered AP duration (APD) being two main endpoints. Clinical evidence has shown that pharmacological treatments can be of more benefit when properly calibrated in a disease‐specific or even mutation‐specific manner (Nebert and Vesell, 2006; Cavallari, 2012; Amin and Wilde, 2016; Itoh et al , 2016; Martiniano et al , 2016).…”
Section: Cardiotoxicity Screening Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hiPSC‐CMs are also being used as model systems to test the effect of both known and novel drugs on cardiac channelopathies (Matsa et al , 2011; Zhang et al , 2012; Bellin et al , 2013; Di Pasquale et al , 2013; Zhang et al , 2014), with suppression of pathological pro‐arrhythmic potential and restoration of altered AP duration (APD) being two main endpoints. Clinical evidence has shown that pharmacological treatments can be of more benefit when properly calibrated in a disease‐specific or even mutation‐specific manner (Nebert and Vesell, 2006; Cavallari, 2012; Amin and Wilde, 2016; Itoh et al , 2016; Martiniano et al , 2016).…”
Section: Cardiotoxicity Screening Methodologiesmentioning
confidence: 99%
“…The green area defines the normal QT interval range for humans. Data are shown as mean ± SD: 1, (Malan et al , 2016); 2, (Rocchetti/Sala et al , unpublished); 3, (Zhang et al , 2014); 4, (Zhang et al , 2014); 5, (Davis et al , 2012); 6, (Rocchetti/Sala et al , unpublished); 7, (Bellin et al , 2013); 8, (Sala et al , 2016); 9, (Bizy et al , 2013); 10, (Ma et al , 2013); 11, (Ma et al , 2015); 12, (Ma et al , 2015); 13, (Gibson et al , 2014a); 14, (Itzhaki et al , 2011); 15, (Gibson et al , 2014c); 16, (Lu et al , 2014); 17, (Gibson et al , 2014b); 18, (Mehta et al , 2014). (B) and (C) Composition of extracellular buffers (B) and pipette solutions (C) for current clamp experiments.…”
Section: Assays and Readoutsmentioning
confidence: 99%
“…Reprogramming of the skin fibroblasts was performed as described previously. 17 In brief, skin fibroblasts derived from a donated biopsy were infected with Sendai virus encoding OCT4, SOX2, KLF4, and MYC and cultured on mouse embryonic feeder cells until hiPSC colonies appeared and could be picked for further expansion and characterization for pluripotency in culture and cryopreserved. A second, non-sex matched, control hiPSC line was generated previously and characterized in detail.…”
Section: Generation Of Patient-specific Hipscsmentioning
confidence: 99%
“…A second, non-sex matched, control hiPSC line was generated previously and characterized in detail. 17 …”
Section: Generation Of Patient-specific Hipscsmentioning
confidence: 99%
“…the slow I Ks , and the rapid I Kr components of the delayed rectifier potassium currents, the sodium current I Na , and the L‐type calcium current I CaL ) varying widely even among wild‐type control hiPSC‐CMs 55, 56. Most notably, very different levels of I Ks have been described (ranging from ~ 0.3 to ~ 2.5 pA/pF 5, 57), variable observation leading to controversial conclusions: on the one hand, I Ks recapitulates physiological behaviour in playing a major role when repolarisation reserve is attenuated 58, 59; on the other, it seems to contribute to repolarisation in hiPSC‐CMs even in the absence of sympathetic stimulation 5, 36, 60, 61. The immature phenotype of all stem cell derivatives including hiPSC‐CMs is probably the reason for this variability but, independent of the cause, it is a limitation to extrapolating results obtained using hiPSC‐CMs to native – healthy and diseased – adult human CMs as discussed below.…”
Section: Pathological Phenotypes and New Mechanistic Insightsmentioning
confidence: 99%